Queer Feminist International Relations: Uneasy Alliances, Productive Tensions - Darcy Leigh (Alternatif Politika)
This article examines the ‘uneasy alliance’ between Feminist IR and Queer IR. The article focuses on three areas of tension and continuity between the fields: (1) sexuality, sexual deviance and gender variance; (2) the roles of liberalism in gendered, sexualized and racialized violence; and (3) binaries relating to sex, gender and sexuality. The article argues that it is around tensions between Queer and Feminist IR that a Queer Feminist IR can be productively articulated. In particular, a Queer Feminist IR should: centre women and femmes as well as sexuality and gender variance; disrupt of binaries and fixed identities without losing the political leverage that sometimes comes with them; and acknowledge entanglements with the institutions Feminist and Queer IR seek to transform while also resisting being neutralized by assimilation.